2019
DOI: 10.3390/ijms20071663
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of Glycoside Hydrolase Family 1 β-glucosidase Genes in Brassica rapa and Their Potential Role in Pollen Development

Abstract: Glycoside hydrolase family 1 (GH1) β-glucosidases (BGLUs) are encoded by a large number of genes, and are involved in many developmental processes and stress responses in plants. Due to their importance in plant growth and development, genome-wide analyses have been conducted in model plants (Arabidopsis and rice) and maize, but not in Brassica species, which are important vegetable crops. In this study, we systematically analyzed B. rapa BGLUs (BrBGLUs), and demonstrated the involvement of several genes in po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 65 publications
0
25
0
1
Order By: Relevance
“…Other species‐specific genes were annotated as cytochrome P450 (27), cysteine/histidine‐rich C1 (32), domain of unknown function (DUF) (76), glycoside hydrolase (22), NAC domains (14), peptidases (40), protein kinases (15), WRKY (15), and zinc finger proteins (35). Many of these putatively function in development and defense (Hwang et al ., 2014; Singh et al ., 2014; Xu et al ., 2015; Dong et al ., 2019) or might be related to seed germination and dormancy (Papi et al ., 2000; Christianson et al ., 2009; Joseph et al ., 2014; Santamaria et al ., 2014; Raineri et al ., 2016; Zhou et al ., 2020), as expected as many seed samples (234 of 294) were included for RNA‐seq data used in this annotation. Since Ae.…”
Section: Resultsmentioning
confidence: 99%
“…Other species‐specific genes were annotated as cytochrome P450 (27), cysteine/histidine‐rich C1 (32), domain of unknown function (DUF) (76), glycoside hydrolase (22), NAC domains (14), peptidases (40), protein kinases (15), WRKY (15), and zinc finger proteins (35). Many of these putatively function in development and defense (Hwang et al ., 2014; Singh et al ., 2014; Xu et al ., 2015; Dong et al ., 2019) or might be related to seed germination and dormancy (Papi et al ., 2000; Christianson et al ., 2009; Joseph et al ., 2014; Santamaria et al ., 2014; Raineri et al ., 2016; Zhou et al ., 2020), as expected as many seed samples (234 of 294) were included for RNA‐seq data used in this annotation. Since Ae.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, the ANTHER27/BETA GLUCOSIDASE 20 ( ATA27/BGLU20 ), which locates to Cluster #7, has no homology with any of the adjacent lipases, but shows co-expression with EXL4–EXL6 ( Reimegård et al , 2017 ). ATA27/BGLU20 has tapetum-specific expression and has been proposed as playing an indispensable role in pollen development ( Rubinelli et al , 1998 ; Dong et al , 2019 ). ATA27/BGLU20 is predicted to be localized to the endoplasmic reticulum (ER) lumen, which makes this protein less likely to be a sporophytic pollen coat protein (sPCP); however, the co-regulation of this gene with the clustered EXLs may indicate an important role in pollen coat metabolism ( Rubinelli et al , 1998 ).…”
Section: Introductionmentioning
confidence: 99%
“…Conserved motif analysis of PbBGLUs found that all the PbBGLUs contain Motif1, 48 PbBGLUs contain motif9, speculated that the two motifs may be related to catalytic activity. To adapt different new functions that are suitable for changes in the environment, gene structure was commonly diversi ed during the evolution of multigene families [47], for Arabidopsis BGLU genes family 13 exon-12 intron organization was considered as the ancestral gene structure, and the pattern with 13 exons was the most common [1,37]. In this study, we had analyzed exon-intron Structures of PbBGLUs and the results suggested that PbBGLU23 and PbBGLU24 contain only one exon, PbBGLU33 contains the most exons (21) and most gene exons range between 10-15, the result suggested that compared with AtBGLUs, PbBGLUs may have some genetic structure diversity.…”
Section: Discussionmentioning
confidence: 99%
“…2 , except that PbBGLU23 and PbBGLU24 have only one exon, the rest contain 7 or more exons, of which PbBGLU33 contains the most exons (21) and most gene exons range between 10-15. These results indicating the possible occurrence of alternative splicing during gene expression, which in turn leads to functional differences between these closely related PbBGLUs [37].…”
Section: Phylogenetic Conserved Motif and Exon-intron Structures Analmentioning
confidence: 91%
See 1 more Smart Citation